PENGARUH MOTIVASI, KOMUNIKASI, DAN LINGKUNGAN KULIAH TERHADAP KEPUTUSAN MEMILIH MELANJUTKAN PENDIDIKAN PADA STIE EKA PRASETYA MEDAN (STUDI KASUS PADA MAHASISWA/I TAHUN AKADEMIK 2017/2018) - Muammar Rinaldi; Shinta Feronica (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
Step by step a person's needs will be obtained, if they are self-motivated. Motivation can arise from within or outside of the self (environment) which is the driving factor towards the goal to be achieved. Motivation that exists in someone is a driving force that will realize a behavior in order to achieve the goals of his satisfaction. Communication has been very important in all aspects of life. Communication is an individual supporting factor to achieve the desired needs. In this study the independent variables are Motivation (X1), Communication (X2), and Lecture Environment (X3) variables. While the dependent variable is the Decision of Choosing (Y).The research methodology used is quantitative descriptive method, the unit of analysis in this study is STIE Eka Prasetya Medan, and the unit of observation is the 2017/2018 Academic Year Student. In this study population 284 students will be taken to the 2017/2018 Academic Year. The sample technique used in the study is Non- probability sampling, namely Purposive Sampling and using the Slovin formula obtained as many as 166 students.The partial results of the study indicate that the Motivation variable partially has a significant effect on the decision of students in the 2017/2018 Academic Year in choosing to continue their education at STIE Eka Prasetya Medan as evidenced from tcount 2.950 > ttable 1.974 and sig value. 0.004 < 0.05. Communication variables partially have no significant effect on student's decision in 2017/2018 Academic Year choosing to continue their education at STIE Eka Prasetya Medan as evidenced from tcount 0.883 < ttable 1.974 and sig value. 0.379 > 0.05. Lecture Environment Variables partially have a significant effect on the decision of students / i 2017/2018 Academic Year choose to continue their education at STIE Eka Prasetya Medan which is proven from tcount 2.769< ttable 1.974 and sig value. 0.006 < 0.05. Motivation, Communication, and Environment Lecture variables simultaneously have a significant effect on the decision of students / i 2017/2018 Academic Year choosing to continue their education at STIE Eka Prasetya Medan as evidenced from the Fcount value > Ftable ie 5.867 > 2.266 and sig value 0.001< 0.05. The decision decision variable is influenced by the Motivation, Communication, and Lecture Environment variables by 8.1%, while the remaining 91.9% is explained by the influence of other factors or variables outside the model such as promotion, price, location, and others that were not discussed in this study.